2021
DOI: 10.1101/2021.05.26.445185
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-Molecule Dynamics of SARS-CoV-2 5’ Cap Recognition by Human eIF4F

Abstract: Coronaviruses initiate translation through recognition of the viral RNA 5′ m7GpppAm cap by translation factor eIF4F. eIF4F is a heterotrimeric protein complex with cap-binding, RNA-binding, and RNA helicase activities. Modulating eIF4F function through cellular regulation or small-molecule inhibition impacts coronavirus replication, including for SARS-CoV-2. Translation initiation involves highly coordinated dynamics of translation factors with messenger or viral RNA. However, how the eIF4F subunits coordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…In general, it is not known at which stage during scanning individual eIF4 factors might dissociate from the PIC. Selective 40S subunit profiling as well as single-molecule studies of translation initiation ( 27 , 42 , 65–67 ) hold great potential in dissecting the assembly pathways of eIF4s along the initiation process, both for specific mRNAs and transcriptome-wide. Such studies will help pin-point the distinct roles of the individual eIF4 factors and their complexes in the different stages of translation initiation on different mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it is not known at which stage during scanning individual eIF4 factors might dissociate from the PIC. Selective 40S subunit profiling as well as single-molecule studies of translation initiation ( 27 , 42 , 65–67 ) hold great potential in dissecting the assembly pathways of eIF4s along the initiation process, both for specific mRNAs and transcriptome-wide. Such studies will help pin-point the distinct roles of the individual eIF4 factors and their complexes in the different stages of translation initiation on different mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of this gene pathway may contribute to downstream effects of antigen presentation and sustained T cell activation [75]. Lastly, the 5 cap of SARS CoV-2 is recognized by Eukaryotic initiation factor 4A-1 (EIF4A1) [76] and is known to be significantly increased in the platelet proteome of COVID-19 patients thought to affect viral replication and downstream activation of platelets, resulting in thrombotic microangiopathy and increased mortality [77]. Collectively, the results of our WGCNA analysis identified a substantial network of dysregulated genes with many downstream effects that are linked to clinicopathologic data.…”
Section: Discussionmentioning
confidence: 99%
“…rather than eIF4E-eIF4G interactions are the main cause for the acceleration eIF4E-cap binding the increased association time of eIF4E during translation initiation, which is consistent with a recent in vivo report suggesting that eIF4G may persist in mRNA and facilitate cap-binding activity 50 . Conversely, another smFRET study found that partial human eIF4G (557-1137) alone slightly affects eIF4E binding kinetics, but the human eIF4F complex substantially changes the eIF4E-cap association 46 . Interestingly, free eIF4A enhances eIF4E cap accessibility via direct eIF4A-RNA contact, which is similar to the role of eIF4G in eIF4E 25 .…”
Section: Smfi Studies In Mrna Circularizationmentioning
confidence: 94%
“…Recognition of eIF4G increases eIF4E's affinity to a cap or cap analog 44,45 . To study the 5' cap-binding kinetics of eIF4E, smFRET was monitored with fluorescently labeled eIF4E in the absence and presence of eIF4G 25,46,47 (Fig. 2a).…”
Section: Smfi Studies In Mrna Circularizationmentioning
confidence: 99%
See 1 more Smart Citation